2012
DOI: 10.3168/jds.2011-5111
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of two doses of ceftiofur crystalline free acid sterile suspension for treatment of metritis in lactating dairy cows

Abstract: The objectives of this study were to evaluate efficacy of a 2-dose regimen of ceftiofur crystalline free acid sterile suspension (CCFA-SS) for treatment of acute metritis in lactating dairy cows under field conditions and to provide additional safety and injection site tolerance data for injections at the base of the ear. Cows at 15 dairies with rectal temperature ≥ 39.5°C and fetid uterine discharge ≤ 10 d postcalving were randomly assigned by blocks of 2, based on order of entry and without regard to parity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 18 publications
9
69
0
Order By: Relevance
“…Recent studies have shown conflicting results on the efficacy of a single dose of long-acting ceftiofur (crystalline fee acid) to reduce the incidence of metritis in cows with risk factors at calving McLaughlin et al, 2013). There are data to support treatment of cows with metritis with ceftiofur or penicillin (LeBlanc, 2008;McLaughlin et al, 2012), but clinical cure is only around 75% to 80% over 10 to 14 days as compared with 62% in untreated cases (Chenault et al, 2004). The impacts of treatment for metritis on subsequent health and reproductive performance are unclear and studies with longer follow-up are needed.…”
Section: Metritismentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown conflicting results on the efficacy of a single dose of long-acting ceftiofur (crystalline fee acid) to reduce the incidence of metritis in cows with risk factors at calving McLaughlin et al, 2013). There are data to support treatment of cows with metritis with ceftiofur or penicillin (LeBlanc, 2008;McLaughlin et al, 2012), but clinical cure is only around 75% to 80% over 10 to 14 days as compared with 62% in untreated cases (Chenault et al, 2004). The impacts of treatment for metritis on subsequent health and reproductive performance are unclear and studies with longer follow-up are needed.…”
Section: Metritismentioning
confidence: 99%
“…Concentrations of drug are not maintained consistently above the target levels in the uterus in cows with metritis (von Krueger et al, 2013). Spontaneous clinical resolution occurs in some cases (Chenault et al, 2004;McLaughlin et al, 2012) and preliminary data suggest that delay of a few days in the onset of treatment of metritis -a 'wait-and-see' approach to allow for spontaneous resolution in perhaps 20% of cases -is worth testing in larger randomized clinical trials.…”
Section: Metritismentioning
confidence: 99%
“…The six articles used for this study were written in English. Of the six articles, five 6,13,[25][26][27] were considered high quality (scores 86, 68, 70, 88, 74) and one 12 was considered intermediate quality (score 51). Three 13,25,27 of the six articles had untreated negative control groups and three 6,12,26 had treated positive control groups.…”
Section: Methodsmentioning
confidence: 99%
“…Efficacy of ceftiofur was measured by clinical cure in the six articles. The clinical cure as a response to treatment was defined as a decrease in rectal temperature alone 6,12,13 ; a combination of a decrease in rectal temperature and absence of fetid vaginal discharge 13,25,26 ; or a decrease in rectal temperature, an absence of fetid vaginal discharge, and no additional antibiotic therapy needed. 27 Other parameters evaluated included reproductive performance, 6,25,26 milk production, 12,24 endometritis, 25 acute-phase proteins, 12 and financial analysis.…”
Section: Ceftiofur For Treatment Of Metritismentioning
confidence: 99%
See 1 more Smart Citation